Observation of dark-bright vector solitons in fiber lasers - Ma, J. (2020)
We report the experimental observation of coherently coupled dark-bright vector solitons in single mode fiber lasers with either normal or anomalous cavity dispersion. The properties of these vector solitons were found to agree well with theoretical predictions based on the coherently coupled nonlinear Schrödinger equations. The experimental results clearly confirmed the existence of a fundamentally new form of optical solitons in coupled nonlinear systems.